ENDOMETRIUM RECEPTIVITY. MАRKERS OF IMPLANTATION - МICHEL Аbou-Abdallah; NATALIA V. Artymuk; MARIA N. Surina (Фундаментальная и клиническая медицина)
The implantation process is very vulnerable and requires a number of conditions: a high degree of synchronism between the endometrium and the embryo, an adequate hormonal environment, normal anatomical conditions and the function of the sex cells. Taking into account the complexity of the process, it is no wonder that frequent implant failures. From a clinical point of view, these failures are becoming an increasingly important problem. Infertility occurs on average for every sixth pair, and this percentage continues to grow.